ATHENIAN TAXES IN THE HELLENISTIC PERIOD. - Fawcett, Peter (Hesperia)
This article surveys modern scholarship on Athenian taxes and tax administration in the Hellenistic period, from the death of Alexander the Great to the sack of Athens by the Romans in 86 bce, and on the benefits that Athens derived from the tax-free island of Delos after 167 bce. I highlight the transition from compulsory to voluntary payments as taxes, and examine continuities and discontinuities in Athenian taxes from the Classical period to the Hellenistic period, as well as their influences on Roman taxes.